Insights into the degradation of (CF3)2CHOCH3 and its oxidative product (CF3)2CHOCHO & the formation and catalytic degradation of organic nitrates. (June 2018) - Bai, Feng-Yang; Jia, Zi-Man; Pan, Xiu-Mei
Abstract: In this work, a systematic investigation of the atmospheric oxidation mechanism of (CF3 )2 CXOCH3 and their oxidative products (CF3 )2 CXOCHO (X = H, F) initiated by OH radical or Cl atom is performed by density functional theory. This study reveals that the introduction of NO and O2 promotes the formation of organic nitrates, which are hygroscopic and are inclined to form secondary organic aerosols (SOA) and can affect the air quality. The rate constants of the individual reactions are found to be in agreement with the experimental results. One of the intriguing findings of this work is that the peroxynitrite of (CF3 )2 CHOCH2 OONO formed from the subsequent reactions of (CF3 )2 CHOCH3 is more favorable to isomerize to organic nitrate (CF3 )2 CHOCH2 ONO2 than to dissociate into alkoxy radical (CF3 )2 CHOCH2 O and NO2 because of the lower energy barrier of isomerization. The second significant observation is that the organic nitrate can be degraded more favorably with the presence of NH3, CH3 NH2, and CH3 NHCH3 than its naked decomposition reaction (CF3 )2 CHOCH2 ONO2 →(CF3 )2 CHOCHO + HONO. The ammonium salt, a vital part of haze, is harmful to human health and can be formed in the existence of the NH3, CH3 NH2, and CH3 NHCH3 . In addition, the toxic substance of peroxyalkyl nitrate (CF3 )2 CHOC(O)ONO2 which can reduce the visibility of the atmosphere is produced as the primary subsequent oxidation product of (CF3 )2 CHOCHO in a NO-rich environment. The main species detected experimentally are confirmed by this study. The computational results are crucial to risk assessment and pollution prevention of the volatile organic compounds (VOCs). Graphical abstract: Image 1 Highlights: Mechanism and kinetics of Cl and OH-initiated oxidation of HFEs are studied. The atmospheric lifetime and GWPs for the HFEs are estimated. Ammonia and amines are important in the degradation of organic nitrates. The possibilities of SOA formation are predicted by DFT.